The acceptance of biogas in Islamic Boarding School Surakarta - Amining Rahmasiwi; Retno Wahyuningsih; Ahmad Muhammad Mustain Nasoha; Septin Puji Astuti (Center for Science and Technology, IAIN Surakarta, 2024)
The rapid population growth in Indonesia is leading to increased energy demands and the depletion of global energy sources. One promising to meet these escalating energy needs in the adoption of renewable energy sources like biogas. This study employs qualitative research methods to measure the response of the Islamic boarding school community in Central Java towards biogas utilization. Data analysis was conducted interactively, narratively describing insights gleaned from questionnaires completed by respondents. The findings reveal a varied response within Central Java Islamic Boarding School Community towards embracing biogas as part of efforts to enhance the national renewable energy mix. However, there is a consensus on certain aspects: respondents generally support biogas utilization as long as it is safe, sourced from clean materials, and developed in suitable locations. The exploration among ten boarding schools suggests that the government’s renewable energy initiatives require further optimization in terms of socialization and engagement with Islamic boarding schools.